Conceptual models for integration of Data Mining and SEO to Improve E-Commerce Performance - Andjarwati, Tri; Hermanto, Agus; Wulan, Vieqi Rakhma (Proceeding UII-ICABE, 2020)
Since the initiation of online trading in Indonesia, the public trust getting higher in using e-business applications have a positive effect, in the form of more open markets and raised competition to gain consumer trust. This requires a concern of company management settling their product sales strategies to continue going up, mainly online trading. At some point, the technique used for online marketing is SEO (search engine optimizer), but in its use, SEO still has some drawbacks. Therefore, in this article it is proposed to carry out data mining integration with SEO, so that the results can be used to improve e- business performance support that can be used as an alternative decision-making by management. Keywords: SEO, data mining, e-commerce, management, marketing